International migration: a panel data analysis of economic and non-economic determinants - Anna Maria Mayda (Institute for the Study of Labor (IZA), 2005)
In this paper I empirically investigate economic and non-economic determinants of migration inflows into fourteen OECD countries by country of origin, between 1980 and 1995. The annual panel data set used makes it possible to exploit both the time-series and cross-country variation in immigrant inflows. I focus on both supply and demand determinants of migration patterns and find results broadly consistent with the theoretical predictions of a standard international-migration model. Both first and second moments of the income distribution in the destination and origin countries shape international migration movements. In particular, I find evidence of robust and significant pull effects, that is the positive impact on immigrant inflows of improvements in the mean income opportunities in the host country. Inequality in the origin and destination economies affects the size of migration rates as predicted by Borjas (1987) selection model. Finally, among the non-economic determinants, I investigate the impact on emigration rates of geographical, cultural, and demographic factors as well as the role played by changes in destination countries' migration policies.
Keywords: F22; 330; international migration; push and pull factors; network effects; Internationale Wanderung; Migrationspolitik; Einkommen; Kultur; OECD-Staaten